Inovasi Kemasan Produk Makanan Dan Minuman Untuk Meningkatkan Nilai Jual Di Desa Wisata - Martini Martini; Nurussama Nurussama; Nabila Kintan Oktadinna (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to demonstrate the transformation and development of local food and beverage product packaging to enhance its uniqueness and appeal, thereby increasing its marketability in tourism villages. This endeavor extends beyond merely preserving product quality and integrity; it also serves as a potent marketing tool. High-quality packaging can strengthen brand image and attract consumer attention, ultimately enhancing the product's visual appeal and sale value. Consequently, such efforts can provide financial support to Micro, Small, and Medium Enterprises (UMKM) within these tourism villages. The research methodology adopts a participatory approach, actively involving the community of the tourism village. Although no immediate change in selling price has been observed, the implementation of this program presents an opportunity for the future adoption of premium pricing strategies. This initiative contributes to the economic development strategy for coastal communities through local product packaging innovation, which has the potential to increase product value through creative and innovative packaging solutions. The conclusion drawn from this activity is the successful implementation of an educational program on product packaging innovation. The target audience, the community, is now better equipped to understand the technology and knowledge related to packaging innovation